Mapping E-Waste Distribution to Form a Circular Supply Chain – An Investigation on E-Waste Towards Circular Economy in Taiwan - Hung, Shu-Hui; Tsai, Kuan-Wei (Applied Environmental Research, 2024)
While there has been a growing number of studies utilizing material flow analysis (MFA) to examine the flow of e-waste, there remains a lack of studies on industrial e-waste circularity in Taiwan. This study employs MFA to examine the annual generation of e-waste by Taiwanese industries, the domestic flow of this waste, the utilization of secondary materials recovered from e-waste, and the spatial distribution of e-waste and its secondary materials. The results reveal that Taiwan generates approximately 50,000 tons of e-waste per year, with waste code E-0221 and the "manufacture of other electronic parts and components" industry being the primary contributors. About 24.46% of the secondary materials derived from e-waste are utilized by e-waste-generated industries. However, the overall cyclical use rate is only 0.07%. This does not imply that the majority of industrial e-waste is not properly recycled. Rather, it suggests that more secondary materials obtained through downcycling, entering other industries. Besides, some manufac-turers process its industrial e-waste in-house, which is not reflected by the cyclical use rate calculated in the study.